Multifunctional components from carbon concrete composite C3 – integrated, textile-based sensor solutions for in situ structural monitoring of adaptive building envelopes. Issue 23 (December 2018) - Haentzsche, Eric; Frauendorf, Moritz; Nocke, Andreas; Cherif, Chokri; Reichardt, Michaela; Butler, Marko; Mechtcherine, Viktor
This contribution will introduce carbon-reinforced concrete components (so-called carbon concrete composites, or C 3 ) with sensor functionalities for innovative building envelopes. For a continuous in situ structural monitoring, these textile-reinforced concrete components are equipped with textile sensor networks consisting of resistive carbon fiber sensors (CFSs), which are integrated into the carbon fiber non-crimp fabrics of the concrete reinforcement by multiaxial warp-knitting. The in situ CFSs, consisting of 1 k or 50 k carbon fiber roving with added staple fiber/multifilament dielectric cladding, are later integral to the load-distributing elements of the concrete component, and elongations within these are easy to record with good correlation to ohmic resistance changes. Gage factors of k  = 0.52–1.23 at linearity deviations of ALin  = 4.0–8.7% are feasible. This allows a monitoring of C 3 building envelopes for structural mechanical changes caused by physical changes within the component through mechanical or thermal loads or deformation and cracks.